Interdisciplinary Oral Rehabilitation of a Teenage Patient with Down Syndrome: A Case Report - Ülkü Tuğba Kalyoncuoğlu; Merve Aksoy; Melek Almıla Erdoğan; Melis Arda Sözüöz (Ankara University, 2023)
Abstract This case report aimed to share the dental rehabilitation of a teenage patient with Down Syndrome who applied to our clinic with aesthetic complaints and to provide a guide to dentists on the treatment options of young syndromic patients with various dental problems.The clinical and radiographic examination of a 17-year-old male patient with Down Syndrome, who applied to the University of Health Sciences, Gülhane Department of Prosthodontics, with aesthetic complaints, revealed the necessity of occlusion regulation and the restoration of the existing teeth. Aesthetic need was taken into consideration and a treatment plan was made with the Department of Pediatric Dentistry. After the extraction of the patient's hopeless teeth, the missing teeth were corrected with a fixed partial denture, taking into account the patient's wishes. Onlay restorations made of 3D printed resins are planned for teeth that remain in infraocclusion. It was planned to restore anterior maxillary teethwith strip crowns in order to achieve aesthetics, and after the root canal treatment Finally, premolar forms were created for the maxillary permanent canine teeth with strip crowns to support the occlusion.The treatment of our patient was completed, and his function and phonation were maintained, as well as achieving the aesthetic he dreamed of.